Benefit finding: understanding the impact and public health factors among COVID-19 patients in China. (24th February 2022) - Wang, Sitong; Zhou, Yanan; Li, Li; Kent, Susan
Abstract : Background: This study aimed to determine the level of benefit finding among COVID-19 patients in a hospital in mainland China, and to identify its associated impact and public health factors. Methods: Using a cross-sectional design, a total of 288 COVID-19 patients were recruited in Huoshenshan Hospital in Wuhan, China to complete a survey on benefit finding. The level of benefit finding evaluated by the Benefit Finding Scale (BFS), mental resilience evaluated by the Connor-Davidson Resilience Scale (CD-RISC), social support evaluated by the Multidimensional Scale of Perceived Social Support (MSPSS), medical coping modes evaluated by the Medical Coping Modes Questionnaire (MCMQ), and general information was collected by self-designed questionnaires. T-test and chi-square test were used for single-factor analyses. For multiple factor analyses, multivariate regression analyses were performed. Result: The mean BFS score of 288 participants was 61.26±10.25. Multivariate regression analysis showed that the factors associated with the level of benefit finding among COVID-19 patients in China included education level, having experienced major event, social support, optimism, confrontive coping and resigned coping mode. Conclusions: In general, the patients with COVID-19 in this study had a middle level of benefit finding. Health professionals should take measures to identify the influencing factors on the quality of the life and take targeted intervention measures.